VALIDITY OF PROPRIOCEPTIVE REHABILITATION FOR ANKLE INSTABILITY BASED ON FREEMAN BOARD TRAINING - Ktaiche, Jamal; Eddine, Hassane Kheir; Yassine, Hadi; Bassal, Ahmad; Kalach, Amal; Hassan, Khodor Haidar (European Scientific Journal, ESJ, 2015)
Background: Ankle joint sprain and the subsequent development of chronic ankle instability (CAI) are commonly encountered by clinicians involved in the treatment and rehabilitation of musculoskeletal injuries. It has recently been advocated that ankle joint post-sprain rehabilitation protocols should incorporate dynamic neuromuscular training to enhance ankle joint sensorimotor capabilities. Objective: up to date, many studies have reported the effects of Proprioception training on ankle joint stability. But fewer who studied the validity of dynamic Proprioception on ankle instability. The purpose of this pilot study was to conduct the effects of a 4-week dynamic neuromuscular training program in addition to the rehabilitation treatment for ankle instability Methods: 26 sportive men were exposed to a progressive 4-week dynamic neuromuscular training program which incorporated postural stability, strengthening, plyometric. The following criteria were considered: Number of shaking of leg in a minute standing on freeman board (one minute stand), Time of balance on freeman board ( balance), Maximal resistance for ankle dorsal flexion, plantar flexion, Inversion and eversion,Muscle reaction for ankle dorsal flexion, plantar flexion, Inversion and eversion. Measurements were rated within 3 trials for each criterion before and after each session for the affected leg. For the non-affected leg same criteria were measured before and after session without applying the rehabilitation protocol Results: a high significant (p=.000<0.05) a progress is noted during rehabilitation protocol,. Results show high correlation between one minute stands and balance; one minute stand and muscle reaction; balance and maximal resistance was significant. Results show non-significance of correlation between muscle reaction and maximal resistance for ankle dorsal flexion, plantar flexion, Inversion and eversion. Moreover, we can notice that training period has had a slight effect on the non-affected side. Conclusions: The 4-week dynamic neuromuscular training program improves the parameters of ankle joint sensorimotor control in an athlete with CAI.